FAPα and αSMA mark different subsets of fibroblasts in normal kidney and conventional renal cell carcinoma - Peterfi, Lehel; Yusenko, Maria V.; Kovacs, Gyula; Beothe, Tamas (Neoplasia, 2023)
Several studies suggested a correlation between cancer associated fibroblasts (CAF) and cancer progression, but data on conventional renal cell carcinoma (cRCC) is still lacking. We aimed to analyse the impact of αSMA positive myo-CAF and FAPα expressing i-CAF on postoperative relapse of cRCC. We applied immunohistochemistry on tissue-multiarray (TMA) containing 736 consecutively operated cRCC without metastasis at the time of diagnosis. We analysed the correlation between the amount and pattern of αSMA and FAPα expressing CAFs and tumour cells and postoperative tumour relapse.
Online veröffentlicht am 11. Dezember 2022
Gesehen am 07.02.2023